Peranan Bappeda Dalam Perencanaan Pembangunan Partisipatif Di Kabupaten Aceh Timur - Rizam, Teuku; Siregar, Nina Siti Salmaniah; Isnaini, Isnaini (Strukturasi: Jurnal Ilmiah Magister Administrasi Publik, 2021)
The purpose of the study was to analyze the role of Bappeda in participatory development planning in the field of facilities and infrastructure. Bappeda constraints in participatory development planning in the field of facilities and infrastructure. This study used descriptive qualitative method. The sample in this study amounted to 5 people. Data collection was obtained from interviews, documentation and observation. The result of the research is that the role of Bappeda in participatory development planning of facilities and infrastructure is not good because of the lack of active communication between Bappeda elements and agencies. The role of Bappeda in the aspect of integrating activities is running well, as can be seen from the OPD that combines similar activities. Aspects of identifying the linkages and interests of the Agency are going well, there is identification of the OPD. The role of Bappeda in formulating the planning for the development of facilities and infrastructure is good because the planning carried out by Bappeda is macro in nature which is contained in the RPJMD. The planning evaluation aspect went well, evaluating the documents as well as holding a Musrenbang. Aspects of giving instructions and guidance went well, there was training and guidance held by Bappeda in development planning. The role of Bappeda from the aspect of active participation in coordination meetings is good, agencies feel that coordination meetings are important for development.